Nouveau voyage aux Indes orientales (1786-1813) - Sonnerat, Pierre (Collection Indologie, 2010)
In this New Journey to East India, begun in 1786 and completed in 1813, Sonnerat sets out tofurnish his readers with the information that he has gleaned through years of travel and research in that country and at the same time to gather together Contemporary European knowledge about India. A Stimulator of ideas, he makes a contribution of his own to knowledge about natural history, and opens the way for the study of physical geography (morphology, climatology, soil survey, hydrography) and human geography. In doing so, he describes the relationship of Indian people with their surroundings by studying the agricultural, industrial and commercial resources of the areas they inhabit and the benefits that they draw from them. The manuscript of this text, which has been untraceable since 1816, was found recently at the Mitchell Library in Sydney, Australia.